Comparing The Anatomy and Physiology of Different Journals Using Meo’s Fish Bone Model - Anievas, Brenda (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: To dissect and compare the structural makeup of articles from SCOPUS, ACI, and a non-indexed journal and to assess the adherence of these articles to MEO’s Fish Bone Model. Methodology: Descriptive Research Design, Combination of Quantitative and Qualitative, Survey Method Main Findings: Scopus articles exhibit a higher degree of compliance with the model, indicating robust structural integrity and content depth. ACI and non-indexed journals show varied levels of adherence, suggesting room for improvement in meeting established scientific writing standards. Moreover, the analysis revealed that the articles share the basic structural framework. However, the Scopus and ACI articles include additional sections indicating a more comprehensive structure. Scopus articles excel in title clarity, abstract quality, and introduction, surpassing those from ACI and non-indexed journals. Novelty/Originality of this study: Comparing the structures of different articles from different journals using MEO’s fish bone model to guide those who are publishing their research papers.